Stimulasi Perkembangan Sosial Emosional AUD Dengan Permainan Mencocokkan Kartu Emoji di Taman Kanak-Kanak Zainuddin Waru Sidoarjo - Annisa Immadulbilad; Husni Abdillah; Kartika Metafisika (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research was conducted to discover children’s undertanding about social emotional through the game of matching emoji cards. The aim of this service is so that children can learn to regulate their emotions This type of research is qualitative case study research. Data collection techniques include observation, interviews and documentation. Based on the results of this service activity, the participants in the play were divided into two groups. Muhammad's group (boys) and Aisyah's group (girls) compete alternately with emojis. Children understand the meaning of given emojis more quickly. They have succeeded in differentiating the types of emotions of the Emoji Card Matching game.